PELATIHAN BERPIKIR KRITIS BAGI KAUM REMAJA DI PANTI ASUHAN YPU - Raja Oloan Tumanggor; Nadia Nashwa Kamila; Anastasya Dumyanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Critical thinking training for adolescents at the Yayasan Prima Unggul (YPU) orphanage was conducted as part of the Community Service Program (PKM) aimed at improving analytical, evaluation, and rational decision-making skills among these adolescents. The background to the implementation of this PKM is based on the conditions of adolescents in the orphanage who face various psychosocial challenges and limitations in developing critical thinking skills, even though these skills are very important to support their independence and success in the future. The PKM implementation method prioritizes an interactive participant engagement model, including group discussions, questions and answers, case studies, and problem-solving simulations, so that participants do not only passively receive material, but actively develop their critical thinking skills through direct experience and collective reflection. During the training, adolescents are guided to recognize elements of critical thinking and apply them in real-life contexts. The implementation results show that this training provides significant benefits in increasing awareness, critical questioning skills, and developing reflective and analytical attitudes of the participants. This training also builds adaptive life skills for adolescents in the orphanage environment, strengthens their self-confidence, and fosters independence in making appropriate decisions in various situations. Thus, this PKM program makes a positive contribution to character development and critical thinking skills for youth at the Prima Unggul Foundation.